Seasonal characteristics of organic aerosol chemical composition and volatility in Stuttgart, Germany - Huang, Wei; Leisner, Thomas (Atmospheric chemistry and physics, 2019)
Abstract. The chemical composition and volatility of organic aerosol (OA) particles were investigated during July-August 2017 and February-March 2018 in the city of Stuttgart, one of the most polluted cities in Germany. Total non-refractory particle mass was measured with a high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS; hereafter AMS). Aerosol particles were collected on filters and analyzed in the laboratory with a filter inlet for gases and aerosols coupled to a high-resolution time-of-flight chemical ionization mass spectrometer (FIGAERO-HR-ToF-CIMS; hereafter CIMS), yielding the molecular composition of oxygenated OA (OOA) compounds. While the average organic mass loadings are lower in the summer period (5.1±3.2 µg m−3) than in the winter period (8.4±5.6 µg m−3), we find relatively larger mass contributions of organics measured by AMS in summer (68.8±13.4 %) compared to winter (34.8±9.5 %). CIMS mass spectra show OOA compounds in summer have O : C of 0.82±0.02 and are more influenced by biogenic emissions, while OOA compounds in winter have O : C of 0.89±0.06 and are more influenced by biomass burning emissions. Volatility parametrization analysis shows that OOA in winter is less volatile with higher contributions of low-volatility organic compounds (LVOCs) and extremely low-volatility organic compounds (ELVOCs). We partially explain this by the higher contributions of compounds with shorter carbon chain lengths and a higher number of oxygen atoms, i.e., higher O : C in winter. Organic compounds desorbing from the particles deposited on the filter samples also exhibit a shift of signal to higher desorption temperatures (i.e., lower apparent volatility) in winter. This is consistent with the relatively higher O : C in winter but may also be related to higher particle viscosity due to the higher contributions of larger-molecular-weight LVOCs and ELVOCs, interactions between different species and/or particles (particle matrix), and/or thermal decomposition of larger molecules. The results suggest that whereas lower temperature in winter may lead to increased partitioning of semi-volatile organic compounds (SVOCs) into the particle phase, this does not result in a higher overall volatility of OOA in winter and that the difference in sources and/or chemistry between the seasons plays a more important role. Our study provides insights into the seasonal variation of the molecular composition and volatility of ambient OA particles and into their potential sources.